On tubular vs. swung surfaces. (January 2016) - Recio, Tomás; Rafael Sendra, J.; Tabera, Luis-Felipe; Villarino, Carlos
Abstract: We determine necessary and sufficient conditions for a tubular surface to be swung, and vice versa. From these characterizations, we derive two symbolic algorithms. The first one decides whether a given implicit equation, of a tubular surface, admits a swung parametrization and, in the affirmative case, it outputs such a parametrization. The second one decides whether a given swung surface parametrization is a tubular surface and, in the affirmative case, it outputs the implicit equation.